Investigating the Relationships Between Mobility Behaviours and Indicators of Subjective Well‐Being Using Smartphone‐Based Experience Sampling and GPS Tracking. Issue 5 (5th November 2020) - Müller, Sandrine R.; Peters, Heinrich; Matz, Sandra C.; Wang, Weichen; Harari, Gabriella M.
Abstract: People interact with their physical environments every day by visiting different places and moving between them. Such mobility behaviours likely influence and are influenced by people's subjective well‐being. However, past research examining the links between mobility behaviours and well‐being has been inconclusive. Here, we provide a comprehensive investigation of these relationships by examining individual differences in two types of mobility behaviours (movement patterns and places visited) and their relationship to six indicators of subjective well‐being (depression, loneliness, anxiety, stress, affect, and energy) at two different temporal levels of analysis (two‐week tendencies and daily level). Using data from a large smartphone‐based longitudinal study ( N = 1765), we show that (i) movement patterns assessed via GPS data (distance travelled, entropy, and irregularity) and (ii) places visited assessed via experience sampling reports (home, work, and social places) are associated with subjective well‐being at the between and within person levels. Our findings suggest that distance travelled is related to anxiety, affect, and stress, irregularity is related to depression and loneliness, and spending time in social places is negatively associated with loneliness. We discuss the implications of our work and highlight directions for future research on the generalizability to other populations as well as the characteristics of places. © 2020 European Association of Personality Psychology